2019
DOI: 10.3390/mi11010034
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Magnetoresistive Biosensors

Abstract: Magnetoresistance (MR) based biosensors are considered promising candidates for the detection of magnetic nanoparticles (MNPs) as biomarkers and the biomagnetic fields. MR biosensors have been widely used in the detection of proteins, DNAs, as well as the mapping of cardiovascular and brain signals. In this review, we firstly introduce three different MR devices from the fundamental perspectives, followed by the fabrication and surface modification of the MR sensors. The sensitivity of the MR sensors can be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 156 publications
(214 reference statements)
0
56
0
Order By: Relevance
“…GMR effect, which was discovered in 1980s, usually happens in a multi-layer structure in which ferromagnetic (FM) and non-magnetic (NM) thin films are deposited alternately [260] , [261] , [262] . However, subsequently studies demonstrated that GMR effect could also happen in inhomogeneous media, granular films for example, which expanded the biomedical applications of GMR biosensors [263] , [264] . Moreover, GMR effect can sense very low magnetic fields, making it very attractive for developing magnetic biosensors for highly sensitive POC detection of infectious diseases.…”
Section: Detection Methods For Poc Diagnostic Applicationsmentioning
confidence: 99%
“…GMR effect, which was discovered in 1980s, usually happens in a multi-layer structure in which ferromagnetic (FM) and non-magnetic (NM) thin films are deposited alternately [260] , [261] , [262] . However, subsequently studies demonstrated that GMR effect could also happen in inhomogeneous media, granular films for example, which expanded the biomedical applications of GMR biosensors [263] , [264] . Moreover, GMR effect can sense very low magnetic fields, making it very attractive for developing magnetic biosensors for highly sensitive POC detection of infectious diseases.…”
Section: Detection Methods For Poc Diagnostic Applicationsmentioning
confidence: 99%
“…The image in part C adapted from ref 69 is licensed under CC BY-ND 2.0. The image in part D adapted from ref ( 70 ) is licensed under CC BY-ND 2.0.…”
Section: Mr Platformsmentioning
confidence: 99%
“… 67 With the advancing of thin-film deposition and nanofabrication technologies, the TMR ratio has increased dramatically during the past 20 years from ∼20% to over 200%. 62 , 68 70 …”
Section: Mr Platformsmentioning
confidence: 99%
“…After the discovery of high magnetoresistance (MR) in ferromagnetic multilayers [ 15 ], MR effect-based sensors, such as anisotropic magnetoresistance (AMR), giant magnetoresistance (GMR), and tunneling magnetoresistance (TMR) sensors, have been widely investigated for the detection of small magnetic fields in various applications [ 16 , 17 , 18 ]. Among these MR sensors, magnetic tunnel junction (MTJ)-based TMR sensors have attracted much attention due to their high MR ratio at room temperature.…”
Section: Introductionmentioning
confidence: 99%